FORMING READINESS TEACHERS OF PRIMARY CLASSES TO THE USED INTERACTIVE TECHNOLOGIES OF TEACHING (Pedagogy of Higher and Secondary Education, 2009)
In this article author examines the state and problems of forming readiness teachers of primary classes to the used interactive technologies of teaching.
Keywords: interactive technologies of teaching; sub'ekt-sub'ekome relation